Is the secret for a successful aging to keep track of cancer pathways?. Issue 11 (15th June 2018) - Tramontano, Donatella; De Amicis, Francesca
Abstract : A successful aging could be gained by life satisfaction, social functioning, or psychological resources and, definitely, by increasing resistance to diverse age‐related pathologies. Nowadays, cancer can be considered an age‐related disease since the incidence of most cancers increases with age, rising more rapidly beginning in midlife. Although adults with extended longevity are less likely to develop cancer, it is now emerging that aging and cancer share common molecular links, and thus targeting these mechanisms may be suitable to treat multiple disorders, for the prolonging of healthy aging. At present, one of the cornerstones of antiaging is hormone‐replacement therapy to treat diseases associated with a state of age‐related sex‐hormone deficiency in women and men; however, many studies question the relationship of hormone replacement to cancer recurrence. Here, we discuss signaling and metabolic molecular crossroad linking aging and cancer. This is useful to argue about the current knowledge of prolongevity and druggable targets and to motivate specific intervention strategies that could modify practices of the aging population, activating multiple longevity pathways but keeping track of cancer pathways, thereby potentially preserving health status. Abstract : In this minireview, we discuss signaling and metabolic molecular crossroad linking aging and cancer. This is useful to argue about current knowledge of prolongevity and druggable targets and to motivate specific intervention strategies that could modify practices of the aging population, activating multiple longevity pathways but keeping track of cancer pathways, thereby potentially preserving health status.